Risk factors and management associated with postoperative cerebrospinal fluid leak after endoscopic endonasal surgery for pituitary adenoma - Li, Bin; Zhao, Sida; Fang, Qiuyue; Nie, Ding; Cheng, Jianhua; Zhu, Haibo; Li, Chuzhong; Gui, Songbai; Zhang, Yazhuo; Zhao, Peng (Frontiers in Surgery, 2022)
Abstract OBJECTIVE To determine risk factors and management for the development of a postoperative cerebrospinal fluid (CSF) leak after an endoscopic endonasal surgery (EES) for pituitary adenomas. METHODS The clinical data of 400 patients who underwent EES for resection of pituitary adenomas from December 2018 to November 2019 in the Department of Neurosurgery of Beijing Tiantan Hospital were retrospectively reviewed. Age, gender, body mass index (BMI), tumor size, Knosp grade, suprasellar extension grade, sellar floor erosion grade, repeated transsphenoidal surgery, intraoperative CSF leak, use of pedicled nasoseptal flap and lumbar drain were collected and analyzed. RESULTS Postoperative CSF leak occurred in 14 of 400 patients (3.5%). Age, gender, BMI, tumor size, Knosp grade and repeated transsphenoidal surgery were not risk factors for CSF leak. Suprasellar extension grade (≥B 6.0% vs.